An ultra scale‐down approach to study the interaction of fermentation, homogenization, and centrifugation for antibody fragment recovery from rec E. coli. Issue 8 (7th May 2013) - Li, Qiang; Mannall, Gareth J.; Ali, Shaukat; Hoare, Mike
Abstract Escherichia coli is frequently used as a microbial host to express recombinant proteins but it lacks the ability to secrete proteins into medium. One option for protein release is to use high‐pressure homogenization followed by a centrifugation step to remove cell debris. While this does not give selective release of proteins in the periplasmic space, it does provide a robust process. An ultra scale‐down (USD) approach based on focused acoustics is described to study rec E. coli cell disruption by high‐pressure homogenization for recovery of an antibody fragment (Fab′) and the impact of fermentation harvest time. This approach is followed by microwell‐based USD centrifugation to study the removal of the resultant cell debris. Successful verification of this USD approach is achieved using pilot scale high‐pressure homogenization and pilot scale, continuous flow, disc stack centrifugation comparing performance parameters such as the fraction of Fab′ release, cell debris size distribution and the carryover of cell debris fine particles in the supernatant. The integration of fermentation and primary recovery stages is examined using USD monitoring of different phases of cell growth. Increasing susceptibility of the cells to disruption is observed with time following induction. For a given recovery process this results in a higher fraction of product release and a greater proportion of fine cell debris particles that are difficult to remove by centrifugation. Such observations are confirmed at pilot scale. Biotechnol. Bioeng. 2013 9999:XX–XX. © 2013 Wiley Periodicals, Inc. Biotechnol. Bioeng. 2013; 110: 2150–2160. © 2013 Wiley Periodicals, Inc.